Rhodium catalyzed hydroformylation - Leeuwen, P. W. N. M. van (Piet W. N. M.); Claver, Carmen (Catalysis by metal complexes, 2000)
This text discusses several rhodium systems arranged according to ligand type, including asymmetric ligands, a chapter on applications in organic chemistry, a chapter on modern processes and separations, and a chapter on catalyst preparation and laboratory techniques.